Sand in the wind - Gear, Kathleen O'Neal (TOR Books, 1990)
A romantic novel set in Montana. Colleen Merrill, drawn by dreams of an Indian warrior, travels to Montana with her brutal husband to establish a homestead. She meets and falls in love with Lieutenant Matthew Douglas, a U.S. Cavalry officer. Wounded Bear, a young Cheyenne warrior and medicine man, has been told in a vision that a golden haired woman has the power to save his people from invasion by the white man. He seeks out this woman and finds Colleen. The two become lovers.